2018
DOI: 10.3389/fphar.2018.00397
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine Receptors in Developing and Adult Mouse Neuromuscular Junctions and Functional Links With Other Metabotropic Receptor Pathways

Abstract: In the last few years, we have studied the presence and involvement in synaptogenesis and mature transmitter release of the adenosine autoreceptors (AR) in the mammalian neuromuscular junction (NMJ). Here, we review and bring together the previously published data to emphasize the relevance of these receptors for developmental axonal competition, synaptic loss and mature NMJ functional modulation. However, in addition to AR, activity-dependent mediators originating from any of the three cells that make the syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 97 publications
(162 reference statements)
1
15
0
Order By: Relevance
“…Another regulator of PKA is A 2A adenosine receptor signaling, which has the opposite effect to M 2 signaling. It stimulates adenyl cyclase and PKA activity [29,59,68]. Thus, the A 2A -mediated increased PKA activity can be expected to cause a delay in axon loss similar to the one observed here when PKA was experimentally directly activated.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Another regulator of PKA is A 2A adenosine receptor signaling, which has the opposite effect to M 2 signaling. It stimulates adenyl cyclase and PKA activity [29,59,68]. Thus, the A 2A -mediated increased PKA activity can be expected to cause a delay in axon loss similar to the one observed here when PKA was experimentally directly activated.…”
Section: Discussionsupporting
confidence: 53%
“…In the NMJ, activity dependent variations of released mediators such as Ach, adenosine, and neurotrophins are sensed by presynaptic mAChR, AR (P1), and the TrkB receptors [17,54,55], as well as ATP receptors (P2) and glutamate receptors [18,19,56,57]. These receptors are coupled to downstream kinases, mainly PKC and PKA, that phosphorylate the protein targets involved in axonal disconnection or consolidation and synapse maturation [29,58,59].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This includes muscarinic acetylcholine autoreceptors (mAChRs) [31][32][33][34][35], TrkB [36] and adenosine receptors (AR) [37]. Moreover, we widely investigated the functional complex network constituted by these receptors and the presynaptic serine-threonine kinases, PKC and PKA, to regulate ACh release at the NMJ [38]. Furthermore, we presented the individual and complementary actions of presynaptic activity and the resulting muscle contraction over presynaptic kinases, and showed that BDNF/TrkB signaling is key in their regulation [36,39,40], which reveals the mutual intercommunication and regulation between the nerve terminal and the myocyte activities.…”
Section: Introductionmentioning
confidence: 99%
“…This may reflect the impairment of the presynaptic Ca 2+ homeostasis for ACh release (Takamori, 2012) to compensate for postsynaptic dysfunction. The presynaptic Ca 2+ homeostasis is promoted by the activation of G protein-coupled receptors such as M1-type muscarinic AChR (M1 mAChR) and A2A adenosine receptor along with the interaction of brain-derived neurotrophic factor (BDNF) with receptor tyrosine kinase B (TrkB); these biological mechanisms lead to P/Q-type VGCC activation by the signaling mediated by phospholipase C (PLC)-phosphatidylinositol 4,5-bisphosphate (PIP2)-diacylglycerol (DAG)-protein kinase C (PKC; Amaral and Pozzo-Miller, 2012;Santafé et al, 2015;Nadal et al, 2016;Hurtado et al, 2017;Simö et al, 2018;Tomàs et al, 2018). Also, PLC-generated DAG regulates the presynaptic vesicle priming protein (Munc13-1) to recruit ACh-containing vesicles for the immediately releasable pool (Bauer et al, 2007).…”
Section: Presynaptic Ca 2+ Homeostasis and Autoreceptorsmentioning
confidence: 99%